From Kerygma Toward Martyria: The Meaning of Human Suffering as a Process of Transformation - Ferry Susanto; Riana Riana (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
The Christian faith seeks to find meaning and value in the very real suffering that is present in human life. This study intends to find the deeper meaning for suffering than just viewing it as a misfortunate. This research will show that the Christian faith enables sufferers not only to overcome their own suffering but also to be transformed, becoming bridges of love to help others who are still struggling with their pain. The methodology used in this research is, literary study, biblical narrative on Gospel of Mark and Theology of Martyria of the author with his work serving the sick people. The suffering holds a transformative goal for those who endure it and the people around them. It takes enlightenment of the mind and heart for a person to discover and become aware of their calling as Christian. Analysis of the thought of C.S. Lewis and the story of demonic man in the Gospel of Mark present a theological perspective on suffering, the believers should not give up in facing of their pain. Finally, the presence of Rumah Teduh Suryo stands as a testimony that faith must be along with concrete action.